Intraoperative Results and Postoperative Clinical Outcomes of Lumbar Microdiscectomy in Patients who Previously Received a Transforaminal Anterior Epidural Steroid Injection for Lumbar Radiculopathy - Ozturk, Sait; Akgun, Bekir; Erol, Fatih Serhat; Onal, Selami Ates; Kaplan, Metin (Turkish Neurosurgical Soc, 2018)
AIM: To describe the intra- and postoperative results of patients who received a transforaminal anterior epidural steroid injection (TAESI) prior to lumbar microdiscectomy. MATERIAL and METHODS: Sixty-four patients who did not improve after minimally invasive techniques (MIT) for lumbar radiculopathy were evaluated. Thirty-two of them treated with techniques other than TAESI and those receiving thrombolytic or anticoagulant drugs before microdiscectomy were excluded. We recorded the type of MIT, numbers of levels and injections, time interval between the last MIT and microdiscectomy, duration of surgery, amount of intraoperative blood loss, rate of incidental durotomy, postoperative infection, and visual analogue scale (VAS) scores for leg pain before and after microdiscectomy at 24 hours, and the 1st and 3rd months (Group 1). A total of 35 patients with no history of MIT or lumbar surgery who had undergone unilateral, single-level lumbar microdiscectomy at our clinic were randomly selected to be included in the control group (Group 2) and same parameters were recorded for the comparison of both groups. RESULTS: The mean duration of lumbar discectomy was 140 minutes, and the amount of average intraoperative blood loss was 227 cc in the study group (Group 1), and 65 minutes and 73 cc, respectively in the control group (Group 2)(p>0.05). The comparison of VAS scores revealed that lumbar discectomy was still effective after TAESI (p=0.00). CONCLUSION: Although epidural steroid injection is an effective modality for the management of chronic pain, these patients should be informed preoperatively about the relatively long duration of surgery and the possible requirement for blood transfusion.
Keywords: Steroid injection; Radiculopathy; Microdiscectomy; Transforaminal; Epidural